Conectividad vial en la gestión territorial: una mirada desde los indicadores sociales - Aronés Cisneros, Angel (2024)
The objective of this research is to analyze road connectivity in relation to the indicators of illiteracy, malnutrition, homes without access to water, non-monetary poverty and internet access. In the methodology for mapping road connectivity, distance weighting or inverse distance weighting (IDW) was used in the ArcGis 10.8 software, while the indicators for the districts have been extracted from GeoPerú. The results indicate that road connectivity plays a crucial role in the socio-economic development of the districts. Those with high connectivity, such as Moche, Huancán and Perené, have lower rates of illiteracy, malnutrition, homes without access to drinking water, non-monetary poverty and homes without internet compared to districts with low connectivity, such as El Porvenir, Santo Domingo de Acobamba and Pichanaqui. It is concluded that road infrastructure is a key factor in reducing inequality and improving living conditions in less developed areas.